Technology for Intercropping in Guava Orchard - R. L. Raut (Current Perspectives in Agriculture and Food Science Vol. 4, 2023)
Guava has a documented history from around fifteenth century. It is an important commercial fruit crop grown in India. This chapter aims to highlight the benefits of Intercropping in guava orchards. Intercropping in guava orchards boosts orchard productivity and fruit quality by enhancing the fertility level of the orchard soil. Intercropping provides farmers with additional income throughout the juvenile stage of the guava plants.